Biodegradation, hemocompatibility and covalent bonding mechanism of electrografting polyethylacrylate coating on Mg alloy for cardiovascular stent. (1st June 2020) - Yang, Yong-Xin; Fang, Zhe; Liu, Yi-Hao; Hou, Ya-Chen; Wang, Li-Guo; Zhou, Yi-Fan; Zhu, Shi-Jie; Zeng, Rong-Chang; Zheng, Yu-Feng; Guan, Shao-Kang
Abstract: Organic coatings are the most widely employed approach for the promotion of corrosion resistance of magnesium (Mg) alloys. Unfortunately, traditional organic coatings are weakly bonded to Mg substrates due to physical adsorption. Herein, a polyethylacrylate (PEA) coating was fabricated on Mg-Zn-Y-Nd alloy via electro-grafting. The surface structure and chemical composition were characterized by means of scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDS), atomic force microscope (AFM) and Fourier transform infrared (FTIR) as well as time of flight-secondary ion mass spectrometer (ToF-SIMS). The results showed that the surface roughness of PEA coating was dominated by scan rate; while the coverage and integrity of PEA coating were mainly affected by the monomer concentration and sweep circles. ToF-SIMS results indicated that PEA coating was wholly covered on Mg alloy, and the presence of C2 H3 Mg − fragment confirmed the covalent bond between PEA coating and Mg alloy. In addition, DFT calculation results of the adsorption of EA molecules with Mg substrate agree well with the experimental phenomena and observation, suggesting that the electrons in 3 s orbit of Mg atoms and 2pz orbit of C1 atom participated in the formation of covalent bond between PEA coating and Mg substrate. Potentiodynamic polarization curves and immersion test demonstrated that the PEA coatings could effectively enhance the corrosion resistance of Mg alloy. The platelet adhesion results designated that platelets were barely visible on PEA coating, which implied that PEA coating could effectively prevent the thrombosis and coagulation of platelets. PEA coating might be a promising candidate coating of Mg alloy for cardiovascular stent.